1983
DOI: 10.1159/000137794
|View full text |Cite
|
Sign up to set email alerts
|

Rebound Insomnia and Rebound Anxiety: A Review

Abstract: Rebound insomnia and rebound anxiety are clinical conditions related to withdrawal of certain benzodiazepine drugs. Numerous studies of benzodiazepine and nonbenzodiazepine hypnotics conducted in our sleep laboratory demonstrated that rebound insomnia developed following withdrawal from benzodiazepines with a rapid or intermediate elimination rate. Several studies conducted by other investigators also indicated the development of rebound insomnia under similar conditions. Rebound insomnia and rebound anxiety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
4

Year Published

1983
1983
2006
2006

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 195 publications
(59 citation statements)
references
References 21 publications
3
52
0
4
Order By: Relevance
“…Rather, rebound insomnia was observed on the first withdrawal night, with a return to baseline values on the subsequent withdrawal nights. Comparable findings have been reported with triazolam, another short acting benzodiazepine hypnotic (Kales et al, 1983;Roth et al, 1983). Similarly, the effects of brotizolam on sleep morphology were observed to be similar to those reported previously with triazolam (Johnson & Spinweber, 1981;Pakes et al, 1981;Roth et al, 1983).…”
Section: Discussionsupporting
confidence: 85%
“…Rather, rebound insomnia was observed on the first withdrawal night, with a return to baseline values on the subsequent withdrawal nights. Comparable findings have been reported with triazolam, another short acting benzodiazepine hypnotic (Kales et al, 1983;Roth et al, 1983). Similarly, the effects of brotizolam on sleep morphology were observed to be similar to those reported previously with triazolam (Johnson & Spinweber, 1981;Pakes et al, 1981;Roth et al, 1983).…”
Section: Discussionsupporting
confidence: 85%
“…The discovery of benzodiazepine receptors in the brain suggests the presence of endoge nous benzodiazepine-like molecules, the pro duction of which would be regulated by con centrations of the circulating molecules or a feedback mechanism [5,86]. Production of endogenous benzodiazepine-like molecules would be decreased if active exogenous ben zodiazepine drugs or metabolites were intro duced.…”
Section: Elimination Ratementioning
confidence: 99%
“…Studies that have specifically examined rumination and insomnia have found a relationship between rumination and sleep quality in both healthy individuals (Thomsen, Mehlsen, Christensen & Zachariae, 2003) and psychiatric patients (Bertelson & Monroe, 1979;Kales, Caldwell, Soldatos, Bixler & Kales, 1983). Thus, there is strong evidence that cognitive arousal at bedtime is associated with increased sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%